Pengaruh Penjualan dan Biaya Operasional terhadap Laba Bersih pada PT Indofood CBP Sukses Makmur Tbk Periode 2012-2021 - Andini Grace Tinia; Anisa Lisara; Elis Badriah (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Profit is one of the main goals of PT Indofood CBP Sukses Makmur Tbk, so that profit becomes an important element in operating all company activities. This study aims to determine and analyze the effect of sales and operating costs on net income at PT Indofood CBP Sukses Makmur Tbk for the 2012-2022 period. This study uses descriptive methods and uses secondary data derived from annual financial reports (annual reports), while the data analysis techniques used to test the data in this study are multiple linear regression analysis, analysis of the coefficient of determination, and significance tests (t-test and t-test). F) using SPSS version 25. The results of the study found that: 1) Sales have a significant effect on net income at PT Indofood CBP Sukses Makmur Tbk for the 2012-2021 period; 2) Operational costs do not have a significant effect on net profit at PT Indofood CBP Sukses Makmur Tbk for the 2012-2021 period; 3) Sales and operational costs have a significant influence on net profit at PT Indofood CBP Sukses Makmur Tbk for the 2012-2021 period. This shows that if sales increase and operational costs decrease, PT Indofood CBP Sukses Makmur's net profit will increase, and vice versa.